In vivo induction of oocyte maturation and ovulation in zebrafish. - Toshinobu Tokumoto; Toshiya Yamaguchi; Sanae Ii; Mika Tokumoto (PLoS ONE, 2011)
The maturation of fish oocytes is a well-characterized system induced by progestins via non-genomic actions. In a previous study, we demonstrated that diethylstilbestrol (DES), a non-steroidal estrogen, induces fish oocyte maturation via the membrane progestin receptor (mPR). Here, we attempted to evaluate the effect of DES as an environmental endocrine disrupting chemical (EDC) upon fish oocyte maturation using live zebrafish. DES triggered oocyte maturation within several hours in vivo when administrated directly into the surrounding water. The natural teleost maturation-inducing hormone, 17alpha, 20beta-dihydroxy-4-pregnen-3-one (17,20beta-DHP) also induced oocyte maturation in vivo. Steroids such as testosterone, progesterone or 17alpha-hydroxyprogesterone were also effective in vivo. Further studies indicated that externally applied 17,20beta-DHP even induced ovulation. In contrast to 17,20beta -DHP, DES induced maturation but not ovulation. Theoretically this assay system provides a means to distinguish pathways involved in the induction of ovulation, which are known to be induced by genomic actions from the pathway normally involved in the induction of oocyte maturation, a typical non-genomic action-dependent pathway. In summary, we have demonstrated the effect of EDCs on fish oocyte maturation in vivo. To address the effects, we have explored a conceptually new approach to distinguish between the genomic and non-genomic actions induced by steroids. The assay can be applied to screens of progestin-like effects upon oocyte maturation and ovulation for small molecules of pharmacological agents or EDCs.